2020
DOI: 10.3389/fmars.2020.00224
|View full text |Cite
|
Sign up to set email alerts
|

What Feeds the Benthos in the Arctic Basins? Assembling a Carbon Budget for the Deep Arctic Ocean

Abstract: Half of the Arctic Ocean is deep sea (>1000 m), and this area is currently transitioning from being permanently ice-covered to being seasonally ice-free. Despite these drastic changes, it remains unclear how organisms are distributed in the deep Arctic basins, and particularly what feeds them. Here, we summarize data on auto-and heterotrophic organisms in the benthic, pelagic, and sympagic realm of the Arctic Ocean basins from the past three decades and put together an organic carbon budget for this region. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 221 publications
(278 reference statements)
0
52
0
Order By: Relevance
“…data), and demersal fish (Majewski et al, 2017;Norcross et al, 2017), with a less pronounced decrease for the smaller meiofauna (≥32 µm -0.5 or 1 mm; Vanreusel et al, 2000;Wei et al, 2010). The underlying reason for benthic biomass declines with depth is primarily the diminishing vertical flux of particulate organic matter (i.e., food particles) with increasing depth (Wiedmann et al, 2020, and references therein). Macrofaunal biomass drops off from peaks of 10-20 g C m −2 on inflow shelves (Grebmeier, 2012), and <1 g C m −2 on the interior Laptev Sea shelf (Vedenin et al, 2018), to an average ∼0.5 g C m −2 at the upper slope and <0.2 g C m −2 at the lower slope (Wlodarska-Kowalczuk et al, 2004;Bluhm et al, 2005Bluhm et al, , 2011Grebmeier et al, 2006;Nelson et al, 2014;Vedenin et al, 2018; estimated from replicate van Veen grab or box core samples at discrete sampling depths).…”
Section: Gradients In Primary Production and Lower Trophic Level Biomassmentioning
confidence: 98%
“…data), and demersal fish (Majewski et al, 2017;Norcross et al, 2017), with a less pronounced decrease for the smaller meiofauna (≥32 µm -0.5 or 1 mm; Vanreusel et al, 2000;Wei et al, 2010). The underlying reason for benthic biomass declines with depth is primarily the diminishing vertical flux of particulate organic matter (i.e., food particles) with increasing depth (Wiedmann et al, 2020, and references therein). Macrofaunal biomass drops off from peaks of 10-20 g C m −2 on inflow shelves (Grebmeier, 2012), and <1 g C m −2 on the interior Laptev Sea shelf (Vedenin et al, 2018), to an average ∼0.5 g C m −2 at the upper slope and <0.2 g C m −2 at the lower slope (Wlodarska-Kowalczuk et al, 2004;Bluhm et al, 2005Bluhm et al, , 2011Grebmeier et al, 2006;Nelson et al, 2014;Vedenin et al, 2018; estimated from replicate van Veen grab or box core samples at discrete sampling depths).…”
Section: Gradients In Primary Production and Lower Trophic Level Biomassmentioning
confidence: 98%
“…Accordingly, field observations show an increased spatial and temporal extent of sea-ice algae and under-ice pelagic phytoplankton in the Arctic basins, for which ocean color based PP assessments are not available 6,[13][14][15] . When the ice melts, such ice-algae and under-ice phytoplankton blooms that are mostly composed of diatoms can also deliver substantial pulses of carbon and nutrients to benthic ecosystems 8,16,17 . For example in 2012, the release of the fast-sinking ice-algae, Melosira spp., from melting sea-ice delivered up to 9 g of carbon per square meter of seafloor, which was more than 85% of the total carbon export that year 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that temperate phytoplankton species will become resident in the Eurasian basins of the Arctic Ocean if the intrusion of warming Atlantic waters continues 7 . As primary producers form the base of the food web, such shifts are likely to have drastic consequences, not just in the pelagic realm, but also for pelagic-benthic coupling and biogeochemical cycling in the Arctic Ocean 8 . However, the complexity of factors driving Arctic productivity regionally makes it difficult to generalize to the future carbon flux in the entire Arctic Ocean 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Oil encapsulation in growing ice can occur over one to two days (Dickens et al 1975;Buist and Dickins 1987;Karlsson 2009), where it may either migrate through the ice at low temperatures (T ice < − 5 °C) (Oggier et al 2019) or remain encapsulated until increased porosity and permeability related to spring warming allows the oil to surface (Dickens et al 1975). The high concentrations of sea-ice biota near the ice/water interface, which contribute substantially to Arctic Ocean primary production (Wiedmann et al 2020), are particularly at risk from under-ice oil exposure. Biological effects of oil have been demonstrated in only a few earlier studies including inhibition of ice-algal growth (Delille and Fiala 1999) and/ or decrease of ice meiofauna abundance (Cross and Martin 1987), but microalgal responses to oil exposure vary markedly.…”
Section: Introductionmentioning
confidence: 99%